Identification and characterization of new proteins crucial for bacterial spore resistance and germination - Yu, Benjamin; Kanaan, Julia; Shames, Hannah; Wicander, James; Aryal, Makunda; Li, Yunfeng; Korza, George; Brul, Stanley; Kramer, Gertjan; Li, Yong-qing; Nichols, Frank C.; Hao, Bing; et al. (Frontiers in Microbiology, 2023)
2Duf, named after the presence of a transmembrane (TM) Duf421 domain and a small Duf1657 domain in its sequence, is likely located in the inner membrane (IM) of spores in some Bacillus species carrying a transposon with an operon termed spoVA2mob. These spores are known for their extreme resistance to wet heat, and 2Duf is believed to be the primary contributor to this trait. In this study, we found that the absence of YetF or YdfS, both Duf421 domain-containing proteins and found only in wild-type (wt) B. subtilis spores with YetF more abundant, leads to decreased resistance to wet heat and agents that can damage spore core components. The IM phospholipid compositions and core water and calcium-dipicolinic acid levels of YetF-deficient spores are similar to those of wt spores, but the deficiency could be restored by ectopic insertion of yetF, and overexpression of YetF increased wt spore resistance to wet heat. In addition, yetF and ydfS spores have decreased germination rates as individuals and populations with germinant receptor-dependent germinants and increased sensitivity to wet heat during germination, potentially due to damage to IM proteins. These data are consistent with a model in which YetF, YdfS and their homologs modify IM structure to reduce IM permeability and stabilize IM proteins against wet heat damage. Multiple yetF homologs are also present in other spore forming Bacilli and Clostridia, and even some asporogenous Firmicutes, but fewer in asporogenous species. The crystal structure of a YetF tetramer lacking the TM helices has been reported and features two distinct globular subdomains in each monomer. Sequence alignment and structure prediction suggest this fold is likely shared by other Duf421-containing proteins, including 2Duf. We have also identified naturally occurring 2duf homologs in some Bacilli and Clostridia species and in wt Bacillus cereus spores, but not in wt B. subtilis. Notably, the genomic organization around the 2duf gene in most of these species is similar to that in spoVA2mob, suggesting that one of these species was the source of the genes on this operon in the extremely wet heat resistant spore formers.